Scarves for Women's Struggles in Argentina - Mira, Julieta (2024)
In March 2020, Nina Brugo and Norita Cortiña – two women who had been protesting in the streets and squares of Argentina for years – fi-nally had something to celebrate in their struggle. They met during one of the many mass demon-strations demanding the right to legal abortion in Argentina, which finally became law in December 2020. Both were wearing scarves on their heads; Nina wore a green scarf to represent the fight for the right to abortion, while Norita wore a white scarf from the Madres de Plaza de Mayo (Mothers of Plaza de Mayo). Their meeting brought togeth-er the past and the present, crystallizing anti-au-thoritarian women’s struggles in Argentina...